NASA's Proposed Budget Sees Small Dip, Emphasizes Innovation and Autonomy in Space. Issue 11 (18th March 2014) - Kumar, Mohi
<x xml:space="preserve">Abstract</x> NASA's proposed federal budget for fiscal year (FY) 2015, released on 4 March, includes new plans to send a probe to Jupiter's icy moon Europa, a ramp up in funding for a mission to redirect an asteroid into near‐Earth orbit, funds to extend the life of the International Space Station (ISS) by at least a decade, and plans to return to the United States the capability to launch astronauts into space, among other highlights.